Constructing landscapes: Health care contexts in rural South Africa (Medicine Anthropology Theory, 2017)
The concept of therapeutic landscapes has been adopted from geography by anthropologists with a similar commitment to addressing the intersections between the construction of place and the multifaceted and symbolic dimensions of health. Drawing from health geography and medical anthropology, we take up the challenge from these fields to approach health broadly in order to understand how health decision making is connected to intersecting political, economic, social, and cultural processes that shape what options are available to people. This article presents findings from an ongoing study of the political ecology of health in northeastern South Africa. We consider how therapeutic landscapes are produced by physical infrastructure, social dynamics, and the use of natural resources for livelihoods and health management. While each of these dimensions is critical in shaping human health, we argue that it is through their interaction that therapeutic landscapes are produced. Landscapes of care are thus complicated and shifting, with rural households making strategic decisions to leverage government support, social support, and resources for health management. We conclude by emphasizing the need for further integration of anthropological and geographic frameworks in studying human health.